Validitas Video Pembelajaran Teks Deskripsi “Wisata Religi Suroboyo” Fase D - M. Azadien Nuzul Zhuhuri; Sujinah Sujinah; Idhoofiyatul Fatin; Tining Haryanti; Eko Suoriyanto (Ideas Publishing, 2023)
In order to lead to the implementation of the Kurikulum Merdeka based on local wisdom at SMP Muhammadiyah 11 Surabaya, valid teaching materials are needed. The purpose of this study was to describe the validity of the learning media in the form of videos using the Powtoon application in the descriptive text lesson on the theme of Suroboyo Religious Tourism elements of writing phase D. The research method used was quantitative with data sources in the form of video assessments from validators through questionnaires. Based on the validation results by the media expert validator, the description text video on the theme of Suroboyo religious tourism is said to be very feasible with an average of 27 and a percentage of 96.4%. Based on material experts, the developed media received an average score of 23.5 which was then percentaged to 73.4%, so that it was included in the feasible category.